MoS2 Confined MXene Heterostructures as Electrode Material for Energy Storage Application. (August 2020) - Chandran, Mijun; Thomas, Anitta; Raveendran, Asha; Vinoba, Mari; Bhagiyalakshmi, Margandan
Abstract: Two-dimensional (2D) titanium carbide Ti3 C2 (MXene) is exemplified as the promising electrode material for supercapacitors. MXene was derived by etching of Al-layer from MAX phase (Ti3 AlC2 ), and MoS2 was confined on MXenes through incipient wet impregnation of MoS2 precursor. The prepared MXene and MoS2 /MXene materials were characterized by X-ray diffraction, scanning electron microscope and energy-dispersive X-ray spectroscopy, BET analysis, and X-ray photoelectron spectroscopy. The electrochemical characteristics of MXene and MoS2 /MXene heterostructures were evaluated by different techniques such as cyclic voltammogram, galvanostatic charge-discharge, and electrochemical impedance spectroscopy. The electrochemical measurements revealed that the maximum specific capacitance of the MoS2 /Mxene electrodes reaches up to 342 F g −1 at a discharge current density of 0.4 A g −1 in an enlarged voltage window of -1.5 V to 1.5 V. Also, Electrochemical impedance studies show that the incorporation of MoS2 decreases the charge transfer resistance of MoS2 /MXene. Overall, the electrochemical performance of MoS2 /MXene exhibited excellent reversibility, cycle stability, and rate performance. The obtained results uncover MoS2 /MXene as promising electrode materials for supercapacitors.